Kewenangan Mahkamah Konstitusi dalam Penyelesaian Sengketa Hasil Pilkada Langsung - Alfret Ananias Bani; Nurianto Rahmat Soepadmo; Ida Bagus Anggapurana Pidada (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia is a constitutional democracy. The authority of the Constitutional Court in examining and deciding cases of disputes over the results of regional head elections has become an old song worked on by the Constitutional Court itself and the Constitutional Court has often withdrawn and canceled its authority in terms of disputes over the results of regional head elections and caused legal uncertainty related to regional head election issues. Then the Constitutional Court ruled that the articles petitioned by the Respondents were contrary to the 1945 Constitution and had no binding legal force. The Constitutional Court is authorized to hear disputes over the results of regional head elections as long as there is no law regulating this matter. Article 1 of Law No. 22/2017 on Regional Head Elections is included in the Election regime, which is carried out directly, publicly, freely, confidentially, honestly and fairly. It is rumored that the 2024 elections will be the cornerstone of the history of simultaneous national elections. This study aims to determine the role of the constitutional court in resolving direct election disputes and to determine the responsibility of special judicial bodies in direct election disputes.